Didactic engineering as a tool for the design of a learning object applied to the teaching of probability (Research, Society and Development, 2019)
This paper deals with an investigation where early stages of Didactic Engineering (DE) are used in the design of a digital resource involving probability content, generating a pedagogical resource. The objective of the research was to conceive a Learning Object as a support for probability teaching. Taking Didactic Engineering as a research methodology, we select specific topics of probability to perform teaching situations. In the Preliminary Analysis phase of Didactic Engineering, two textbooks adopted in a teaching situation were selected to verify how the approach is given to this topic. In addition, an analysis was performed on the National Curriculum Parameters (NCPs), Enem Reference Matrix and the Common Curriculum Base (BNCC) as a way to examine the recommendations of the official documents. Thus, in order to assist the teaching practice of the mathematics teacher, a Learning Object called “Mathematical Casino” was conceived that proposes situations in which the teacher may work the concept as: random experiment and the probability of occurrence of a certain event. Finally, it is understood that this technological apparatus can contribute to student teaching and learning and the implementation of digital resources in class.